Congregational pastoral care through the lens of the Belhar Confession - Mouton , Dawid P (Stellenbosch Theological Journal, 2024)
The Confession of Belhar, adopted in 1986 in response to the brutal and traumatic impacts of apartheid and the ensuing faith crisis of the church, demonstrates a deep sense of care for the other. It calls believers to stand with and act on behalf of those in need. Its call to stand with and as God with the downtrodden and marginalized is a call for collective and collaborative care in service of God and His creation. Through its development and content, the confession’s theology offers a potential framework for a community-oriented congregational pastoral care ministry. In this article, the author explores the development process and the content of the Confession of Belhar and argues that, as a statement of faith, the confession guides in terms of both the essence and process of a congregational pastoral care ministry.